Control system of automatic garage using programmable logic controller - K. Selvakumar; R. Palanisamy; Patti Nikhil; D. Karthikeyan; D. Selvabharathi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
In today’s populated world, urban land availability has become scarce and manual involvement of humans for a proper task makes a work less efficient and less accurate. The garage is one of the workstations which needs to be modernized for enhanced land utilization, energy saving approach and systematic functioning. This goal can only be achieved through the automation of parking systems. We have proposed an automated control system for garage using siemens PLC (programmable logic control)-1200 to control the vehicles. The number plate of the car is recorded through the RFID reader and the parking slot for that particular vehicle is allotted automatically based on the available vacancy. Along with this the parking area is fitted with fire alarm, which will raise if any smoke or fire happens in the location. The total parking cost of each vehicle can be calculated based on the number of hours it has been parked. And the information will be displayed in the SCADA screen. Additionally, instead of the full lightening of the complete place, lightening will be provided only in the direction of movement of the car, preventing wastage of energy.